Cardiometabolic Health: Key in Reducing Adverse COVID-19 Outcomes - Rajiv Chowdhury; Kim R. van Daalen; Oscar H. Franco (Ubiquity Press, 2020)
Whilst current public health measures focused on good hygiene practices and limiting person-to-person transmission contribute effectively in managing the COVID-19 pandemic, they will not prevent all individuals from becoming infected. Thus, it is of importance to explore what individuals could do to mitigate adverse outcomes. The value of beneficial health behaviours and a healthy lifestyle to improve immune functioning and lower adverse consequences of COVID-19 are increasingly being emphasized. Here we discuss seven key health behaviours and corresponding recommendations that may assist in reducing unfavourable COVID-19 outcomes.